(untitled) (Praxis Educativa, 2020)
The Research Methodology course is part of the curriculum of many undergraduate, graduate and postgraduate careers, in very different professional areas and disciplines. In university undergraduate courses in Sociology, Research Methodology constitutes one of the main axes of curriculum design, and several subjects usually cover this area. In this article, from the survey of study plans of different Sociology programs and of the subject syllabuses related to research methodology, we describe some differences in the curricular organization and the implications of these variants in the transmission of methodological knowledge in the training of sociologists.